Unprecedented observation and characterization of sulfur-centred bifurcated hydrogen bonds. Issue 46 (22nd November 2021) - Ma, Xiantao; Zhu, Yingying; Yu, Jing; Zhao, Geng; Duanmu, Jiaxin; Yuan, Yiyun; Chang, Xue-Ping; Xu, Dongli; Zhou, Qiuju
Abstract : It is observed that the sulfur atom can unprecedentedly serve as a good acceptor to form the O–H⋯S⋯H–O bifurcated H-bond. Abstract : Owing to the small electronegativity of the sulfur atom, it is commonly supposed that at most one weak H-bond can be formed between a sulfur atom and an H-bond donor. In this paper, an unprecedented 2 : 1 binding species generated from two molecules of phenol and a molecule of thioether was observed and characterized by various nuclear magnetic resonance (NMR) techniques, Fourier transform-infrared (FT-IR) techniques and density functional theory (DFT) calculations, revealing the formation of sulfur-centred O–H⋯S⋯H–O bifurcated H-bonds. This work may provide a simple and efficient method for the quantitative analysis of weak H-bonds between small organic molecules.